Teachers' Efforts to Increase Student Learning Motivation in PAI Learning - An'nisa Raudhatul Jannah; Muhammad Abdullah Darraz; Ai Fatimah Nur Fuad (Universitas Muhammadiyah Enrekang, 2024)
Motivation is an important factor in determining student learning success. The aim of this research is to analyze and determine teachers' efforts to increase students' motivation to learn Islamic Religious Education. Research setting took place at Dharma Karya Vocational School, specifically for class XI students. The focus of this research, apart from discussing teachers' efforts to increase students' learning motivation, is also aimed at analyzing various obstacles or barriers experienced by students while participating in the Islamic Religious Education Learning process. The type of research used in this research is field research using a qualitative approach with descriptive study methods. The primary data source for this research is the PAI Teacher at Dharma Karya Vocational School. The secondary data source in this research is Dharma Karya Vocational School students, which includes class XI students. Research data collection instruments use interview, observation and documentation techniques. Then the data was analyzed through data reduction techniques, data presentation and data verification. The results of this research conclude that the efforts of Islamic religious education teachers in increasing students' learning motivation in class Then, give assignments to individual students, give praise (appreciation) to students who answer questions correctly, and give marks to each Islamic religious education learning exercise.